THE EFFECT OF AUDIT DELAY, AUDIT TENURE AND FINANCIAL DISTRESS ON AUDITOR SWITCHING: (Empirical Study of Food and Beverage Subsector Manufacturing Companies Listed on the Indonesia Stock Exchange 2017-2021) - Loviera, Windy; Akhsani, Novi (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
In the realm of corporate governance and financial reporting, the relationship between companies and auditors plays a pivotal role. Auditors, as independent third parties, examine a company's financial records to ensure accurate reporting. Auditor switching, the act of a company changing its external auditor, is influenced by factors like audit delay (the time between year-end and audit report issuance), audit tenure (the duration of auditor-company engagement), and financial distress (companies facing financial difficulties). The Indonesia Stock Exchange (IDX) hosts a diverse array of Indonesian companies, including those in the Food and Beverage sector. This study aims to examine the impact of Audit Delay, Audit Tenure, and Financial Distress on Auditor switching in manufacturing companies listed on the Indonesia Stock Exchange during the 2017-2021 period. The study's target population consists of companies within the Food and Beverage sector that are listed on the IDX during the specified period. The sampling technique employed in this research is purposive sampling, resulting in a selection of 10 sample companies over a five-year period, thus providing a dataset of 50 observations. Data analysis employs logistical analysis. The study's findings reveal that, when considered individually, the Audit Delay variable does not significantly influence Auditor Switching. However, Audit Tenure does have an impact on auditor switching, while Financial Distress does not. When analyzed collectively, the variables Audit Delay, Audit Tenure, and Financial Distress demonstrate a significant combined influence on Auditor Switching.